Case Report: Leiomyosarcoma of the inferior vena cava presenting as a right atrial mass: the value of multimodality imaging - Ann-Sophie Eggers; Jelena Jovanić; Stefan Pahl; Cyrill Meuwly; Bojana Ilić; Christoph Philipp Kemna; Patrick Doeblin; Stefanie Maria Werhahn; Ingo Hilgendorf; Sebastian Kelle (Frontiers in Cardiovascular Medicine, 2026)
Leiomyosarcoma of the inferior vena cava (IVC) is a rare malignant tumor that may extend into the right atrium and mimic a primary cardiac neoplasm. Because clinical presentation is often non-specific and depends on tumor location and extent, diagnosis may be delayed, particularly in acute settings with suboptimal imaging conditions. We report the case of a 33-year-old woman presenting with progressive dyspnea, ascites and peripheral edema consistent with right-sided heart failure. Initial contrast-enhanced computed tomography, performed to exclude pulmonary embolism, suggested a right atrial myxoma. However, stepwise multimodality imaging including transthoracic and transesophageal echocardiography, multiphasic computed tomography (CT), and cardiac magnetic resonance imaging (CMR) revealed a large intravascular mass originating from the IVC with contiguous extension in the right atrium, causing near-complete luminal obstruction of atrium and IVC. CMR was essential in establishing the diagnosis by demonstrating tumor continuity, tissue heterogeneity, and malignant enhancement patterns. Histopathological analysis confirmed a low-grade spindle cell leiomyosarcoma (G2, Ki-67 approximately 40%). Staging with multiphasic CT and magnetic resonance imaging of the brain excluded distant metastases. The patient was initiated on neoadjuvant chemotherapy with doxorubicin and ifosfamide with planned surgical resection. This case illustrates the importance of multimodality imaging, with CMR playing a central role, in distinguishing malignant intravascular tumors from benign intracardiac masses. Early diagnosis and a multidisciplinary approach are essential for optimal management.